The impact of static stretching on training performance of competitive swimmers - Henrich, T. W. (Research Quarterly for Exercise and Sport, 2005)
Es wurde untersucht, welchen Einfluss statisches Stretching auf die Trainingsleistung von Schwimmern ausübt.